A Systematic Review of Meta-Analyses in Special Education: Exploring the Evidence Base for High-Leverage Practices. (October 2022) - Nelson, Gena; Cook, Sara Cothren; Zarate, Kary; Powell, Sarah R.; Maggin, Daniel M.; Drake, Kevallyn R.; Kiss, Allyson J.; Ford, Jeremy W.; Sun, Lin; Espinas, Daniel R.
It is crucial that special education teachers are equipped with the knowledge and skills necessary to improve outcomes for students with disabilities. Despite federal legislation and efforts of the field to identify and disseminate evidence-based practices for students with disabilities, it is uncertain whether all special education teachers provide instruction based on the best available research. To better prepare special education teachers, McLeskey et al. proposed 22 high-leverage practices (HLPs). We conducted this systematic review of meta-analyses to provide an initial investigation of the experimental evidence reporting on the effectiveness of the HLPs for students with, or at risk for, a disability. Results indicated the largest amount of evidence from meta-analyses related to intensive instruction, explicit instruction, and social skills, with few meta-analyses reporting on collaboration and assessment. The results highlighted disproportional evidence according to disability categories. Implications for future research, practice, and teacher education are discussed.